2000
DOI: 10.1073/pnas.97.26.14067
|View full text |Cite
|
Sign up to set email alerts
|

Constant mean curvature surfaces with three ends

Abstract: We announce the classification of complete almost embedded surfaces of constant mean curvature, with three ends and genus zero. They are classified by triples of points on the sphere whose distances are the asymptotic necksizes of the three ends. Surfaces that minimize area under a volume constraint have constant mean curvature (CMC); this condition can be expressed as a nonlinear partial differential equation. We are interested in complete CMC surfaces properly embedded in ‫ޒ‬ 3 ; we rescale them to have mean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The development of the technique of surface gluing and the construction of constant mean curvature surfaces with Delaunay ends has led to powerful methods in Geometric Analysis, see the paper of N. Kapouleas [22] and the papers of R. Mazzeo, F. Pacard and D. Pollack [26,27]. A related situation is the study of coplanar end surfaces, see the papers by C. Cosin and A. Ros [7], K. Große-Brauckmann, R. Kusner and J. Sullivan [20] and that of these authors joint with N. Korevaar and J. Ratzkin [19]. An other very powerful tool in Geometric Analysis is the use (often for comparison with the maximum principle) of the catenoid, a very well known unbounded minimal surface of revolution.…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…The development of the technique of surface gluing and the construction of constant mean curvature surfaces with Delaunay ends has led to powerful methods in Geometric Analysis, see the paper of N. Kapouleas [22] and the papers of R. Mazzeo, F. Pacard and D. Pollack [26,27]. A related situation is the study of coplanar end surfaces, see the papers by C. Cosin and A. Ros [7], K. Große-Brauckmann, R. Kusner and J. Sullivan [20] and that of these authors joint with N. Korevaar and J. Ratzkin [19]. An other very powerful tool in Geometric Analysis is the use (often for comparison with the maximum principle) of the catenoid, a very well known unbounded minimal surface of revolution.…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…and so the condition H = 1 leads to the equation (3)(4) pu-^l + pb + il + pff/^O, while the condition H = -1 yields (3.5) ^_I ( l + /9 2 ) _ (1 + p 2 ) 3/2 = 0 P There are two special solutions of (3.4) that can be determined immediately. The first is the constant solution pi = 1, the cylindrical graph of which is the cylinder of radius 1.…”
Section: Definition and Basic Equationsmentioning
confidence: 99%
“…Recently, Kusner, Grosse-Brauckmann and Sullivan have shown that modulo Euclidean motions, .Mo,3 is a 3-ball [4]; it is plausible from their work that this particular moduli space contains no degenerate elements.…”
Section: G K = ML K L>ml K Um^kmentioning
confidence: 99%
“…These force vectors on the ends must sum to zero. This balancing condition is the essential ingredient in classifying such CMC surfaces, and combined with some spherical trigonometry can lead to a complete classification of the three-ended surfaces [5,6].…”
Section: Jy Jdmentioning
confidence: 99%